Cesarean section : understanding and celebrating your baby's birth - Moore, Michele (Johns Hopkins Press health book., 2003)
Annotation One in four babies born in the United States and Europe comes into the world via Cesarean section. Yet this procedure has been described by critics as an unnecessary and potentially dangerous medical intervention. Consequently, expectant mothers often fear this option, and women who have had C-sections can feel a sense of failure. In Cesarean Section: Understanding and Celebrating Your Baby's Birth, Drs. Michele Moore and Caroline de Costa emphasize the joy of delivering a healthy baby, however that is best achieved. They explain why Cesarean births are sometimes preferable to vaginal delivery for both mother and baby, and they help women understand the issues behind the decision to perform the procedure. From anesthesia, surgery, and recovery through at-home care of mother and child, the authors offer reassurance and practical information for all mothers and mothers-to-be. They also discuss the latest findings on postpartum depression and planning for future births, including the possibility of vaginal birth after a Cesarean section. For every woman who has a planned - or unplanned - Cesarean section, this book provides the information they need to alleviate their fears and come to value this delivery option."Because up to a quarter of all births are Cesarean births, prenatal preparation should include information about Cesarean sections for every woman. And that is why we have written this guide ... We believe strongly that it is time to speak out and say that Cesarean section is a normal birth method and that women who have a Cesarean section should not be made to feel that they have failed ... We hope you find the information in this book useful and helpful in thinking about C-section, whether you have already had a Cesarean and want to understand the experience better, you wish to plan for another C-section birth, or you are expecting a baby and want to be informed about all the possibilities ahead, including this other normal way of bringing a baby into the world."--The Introduction.